2010
DOI: 10.1242/jcs.076828
|View full text |Cite
|
Sign up to set email alerts
|

Control of ciliogenesis by FOR20, a novel centrosome and pericentriolar satellite protein

Abstract: On page 2396, the correct wording in the last sentence should be 'greater that with'. The full sentence reads: PCM1 solubility in this case is greater than with nocodazole treatment, probably because large aggregates of satellites form after nocodazole treatment and prevent PCM1 from complete solubilization. We apologise for this mistake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 0 publications
11
17
0
Order By: Relevance
“…Immunofluorescence staining showed that FOR20 colocalized with the centrosomal proteins γ-tubulin and centrin-2 (Supplementary information, Figure S1C), which was validated by co-purification of FOR20 and γ-tubulin in the centrosomal fraction by sucrose gradient centrifugation (Supplementary information, Figure S1D). These results are consistent with the previous studies [11,12]. Next, we used vector-based RNAi to deplete endogenous FOR20 in mammalian cells.…”
Section: The Role Of For20 In S-phase Progressionsupporting
confidence: 92%
See 2 more Smart Citations
“…Immunofluorescence staining showed that FOR20 colocalized with the centrosomal proteins γ-tubulin and centrin-2 (Supplementary information, Figure S1C), which was validated by co-purification of FOR20 and γ-tubulin in the centrosomal fraction by sucrose gradient centrifugation (Supplementary information, Figure S1D). These results are consistent with the previous studies [11,12]. Next, we used vector-based RNAi to deplete endogenous FOR20 in mammalian cells.…”
Section: The Role Of For20 In S-phase Progressionsupporting
confidence: 92%
“…Recently, an evolutionally conserved protein, FOR20 (FOP-related protein of 20 kDa), has been identified; it is associated with centrosomes and may be involved in ciliogenesis [11,12]. Here, we find that FOR20 is essential not only for S-phase progression, but also for recruiting Plk1 to centrosomes.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…To determine whether the pCCCs are likely to be centriole components, we transiently expressed N-and C-terminally GFPtagged human orthologs of each pCCC in U2OS and HeLa human 4026 Journal of Cell Science 123 (23) cell lines and used antibodies recognizing g-tubulin to highlight centrosomes. To the eight unknown gene products, we added one whose homolog localizes to the base of the cilia of Caenorhabditis elegans (B9D2) and one that has only very recently been characterized in human cells (MOT52, also known as FOR20 or BBC20) (Sedjai et al, 2010). Five of the ten tagged proteins showed either diffuse cytoplasmic GFP or bright foci likely to be inclusion bodies (data not shown).…”
Section: Verification Of Putative Centriole Genesmentioning
confidence: 99%
“…Recently, the human ortholog (FOR20) was reported to localize to pericentriolar satellites and to be involved in ciliary assembly (Sedjai et al, 2010). FOR20 is predicted to have a FOP dimerization domain (Pfam domain PF09398), required for the centrosomal localization of the FOP protein (Mikolajka et al, 2006).…”
Section: Verification Of Putative Centriole Genesmentioning
confidence: 99%